Immigrants and entrepreneurship - Magnus Lofstrom (IZA World of Labor, 2014)
Immigrants are widely perceived to be highly entrepreneurial, contributing to economic growth and innovation, and self-employment is often viewed as a means of enhancing labor market integration and success among immigrants. Accordingly, many countries have established special visas and entry requirements to attract immigrant entrepreneurs. Research supports some of these stances, but expectations may be too high. There is no strong evidence that self-employment is an effective tool of upward economic mobility among low-skilled immigrants. More broadly prioritizing high-skilled immigrants may prove to be more successful than focusing on entrepreneurship.
Keywords: J15; J18; J31; J38; J61; L26; M13; 330; entrepreneurship; self-employment; innovation; immigrants; immigration